INVESTIGATION OF DYNAMIC CHARACTERISTICS OF GONDOLA CARS ON PERSPECTIVE BOGIES - Myamlin, S. V.; Bubnov, V. M.; Pysmennyi, Ye. O. (Science and Transport Progress, 2014)
Purpose. In this paper, it is necessary to examine the dynamic properties of the gondola car with bogies, model 18-1711 when it moves on straight and curved sections of a track. Methodology. The calculations were performed using the object-oriented programming on the program "Dynamics of Rail Vehicles" ("DYNRAIL" Myamlin S.V. registered 20.03.2003). Mathematical models of a gondola car and bogies 18-100 and 18-711 were created for the calculations. Findings. Dynamic performances comparison of the gondola car with bogies 18-1711 and the gondola car with bogies 18-100, obtained by calculation method was carried out. Originality. Firstly calculations in order to determine the dynamic properties of the gondola car with bogies 18-1711 when it moves on straight and curved sections of track were performed. At the same time an assessment of the dynamic characteristics of the gondola car was made. The following dynamic standards were determined: the coefficient of vertical dynamics (Cdv), the coefficient of horizontal dynamics (Cdh), and the safety factor against derailment (SFd). Track irregularities in vertical and horizontal transverse planes were assigned as perturbations. They should be so that the dynamic indexes of the widely used in operation gondola car on bogies model 18-100 keep in admissible range of speeds up to 80km / h for the empty gondola car and at speeds up to 90km / h for the loaded gondola cars. Practical value. As a result of the calculations and comparisons of their results, we have findings that the use of bogies with bilinear characteristic of the central suspension will improve the dynamic performances of gondola cars, currently operating on bogies, model 18-100. And by improving the dynamic performances it is possible to increase the permissible speeds of these cars motion.